Modeling of liquid propellant combustion chamber - Pandit, Ajinkya V.; Kumar, Ashok; Rao, G. Srinivasa; Kedarnath, C.; Srihari, R.; Ranade, Vivek V. (Chemical Engineering Journal, 2012)
Liquid propellants are fuels which do not require external supply of oxygen for combustion. These fuels are widely used for propulsion applications in oxygen rare environments (underwater, space). We had previously presented a model for solid propellant decomposition in a combustion chamber. In this study we extend the model for the case of combined solid and liquid propellant combustion. Sub-models relating to solid propellant combustion and outlet flow-rate in the present study are borrowed from the previous study. The combustion chamber is assumed to be a `well-mixed reactor'. A model is developed to characterize the liquid propellant spray assuming the spray is a collection of individually burning droplets. A single droplet decomposition model was developed and used along-with the spray model to solve for the liquid propellant burning rate. Appropriate numerical methods and computer programs were developed to solve the model equations. The model predictions were compared with the experimental data obtained in earlier studies. Appropriate methodology for calibrating the model parameters was developed and its usefulness was demonstrated by comparing the simulated pressure profiles with the experimental pressure profiles. The presented model and results will be useful for selecting appropriate liquid propellants for propulsion systems and for the development of a system level model of propulsion systems. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Liquid propellant; Single droplet decomposition; Spray combustion